Highly Sensitive Detection of Complicated Mutations of Drug Resistance in Mycobacterium tuberculosis Using a Simple, Accurate, Rapid, and Low‐Cost Tailored‐Design Competitive Wild‐Type Blocking Assay (Small Methods 3/2023). Issue 3 (13th March 2023) - Yan, Mengqiu; Zhao, Zhenzhen; Wu, Tao; Liu, Tangyuheng; Xu, Gaolian; Xu, Hong; Ying, Binwu
Abstract : Highly Sensitive Detection In article number 2201322, Xu, Xu, Ying, and co‐workers established a high‐sensitive tailored‐design competitive wild‐type blocking assay for detecting as low as 1% complicated mutations of drug resistance in mycobacterium tuberculosis and its excellent sensitivity and specificity was validated on actual clinical samples. The simplicity, accuracy, rapidity, and low cost of the assay allow for great potential for clinical application, especially in high tuberculosis burden countries.